Decision Support System for Proposing PIP Scholarship Recipients at SMKN 1 Borong Using TOPSIS Method - Alberta Elita Epil; I Putu Agus Eka Darma Udayana; Ni Luh Putu Labasariyani; Putu Gede Surya Cipta Nugraha; Ni Putu Eka Kherismawati (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
Decision support system is a computer-based system in solving management problems so as to produce the best alternative in making a decision. SMKN 1 Borong is a vocational high school located on Jl.Kihajar Dewantara, Satar Peot Village, Borong District, East Manggarai Regency, East Nusa Tenggara. The school was officially established on August 16, 2007 and currently has a total of 800 students. Based on the interview with Mr. Agustinus Galvan Dalory as the principal of SMK Negeri 1 Borong. SMK Negeri 1 Borong is one of the schools that receives the Indonesia Smart Program (PIP) scholarship assistance from the government. The school that handles this scholarship has difficulty selecting the names of scholarship recipients due to the large number of students. In addition, the selection of candidates for PIP scholarships at SMKN 1 Borong in assessing each criterion has not used a decision method. This can lead to errors in awarding the scholarship, resulting in inappropriate distribution of scholarships. To overcome these problems, a Decision Support System (SPK) is needed. One of the SPK methods that can be used is the Technique For Orders Preference By Similarity To Ideal Solution (TOPSIS) method. This method is used to select the best scholarship recipient from several prospective recipients who have their own advantages and disadvantages. The results of the decision support system are able to help the data management process and facilitate decision making.